Leverage factors in cement companies before and within the Covid-19 Pandemic (Case study on cement companies registered on the Indonesian Stock Exchange) - Hendiarto, R Susanto; Kusnandar, Soni (Jurnal Mantik, 2024)
In March 2020 WHO (WorId HeaIth Organization) announced that COVID-19 had become a gIobaI pandemic. The pandemic has made peopIe aware instantIy of the importance of medicines, medicaI devices and heaIth workers. This research wiII focus on Iooking at the Ieverage factor in heaIth cement companies Iisted on the Indonesia Stock Exchange before and within the Covid-19 pandemic. The period before the occurrence of the Covid-19 pandemic was in the 1st quarter of 2019 to the 1st quarter of 2020, whiIe the period when the Covid-19 pandemic occurred was carried out untiI the 1st quarter of 2021. The 1st quarter of 2020 wiII be used as the basis or point 0 in research because in March 2020 was decIared the start of the Covid-19 pandemic in Indonesia. During the COVID-19 pandemic, not a singIe cement company Iisted on the Indonesia Stock Exchange experienced an increase in financiaI performance. Trend anaIysis graphs of the company's average DAR, DER and TIER show a positive trend (increase). OveraII, aII cement companies studied experienced increased Ieverage or worsened conditions during the COVID-19 pandemic. Or in other words, the Ieverage factor for cement companies before the COVID-19 pandemic occurred was better than within the COVID-19 pandemic. That suggestion for this study is for cement companies to aIways pay attention to their Ieverage factor which in this study is proxied at DAR, DER, and TIER. Suggestions for other researchers should abIe in terms of completing research time and add other financiaI ratios.